2016
DOI: 10.1017/s175173111600001x
|View full text |Cite
|
Sign up to set email alerts
|

Dietary supplementation of pyrroloquinoline quinone disodium protects against oxidative stress and liver damage in laying hens fed an oxidized sunflower oil-added diet

Abstract: The protective effects of dietary pyrroloquinoline quinone disodium (PQQ.Na 2 ) supplementation against oxidized sunflower oil-induced oxidative stress and liver injury in laying hens were examined. Three hundred and sixty 53-week-old Hy-Line Gray laying hens were randomly allocated into one of the five dietary treatments. The treatments included: (1) a diet containing 2% fresh sunflower oil; (2) a diet containing 2% thermally oxidized sunflower oil; (3) an oxidized sunflower oil diet with 100 mg/kg of added v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…The use of PQQ in nutrition is increasingly being discussed in the literature ( 8 , 12 ) . There are several studies that have found beneficial effects of PQQ supplementation on the growth performance or body composition of growing rats ( 18 , 19 ) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of PQQ in nutrition is increasingly being discussed in the literature ( 8 , 12 ) . There are several studies that have found beneficial effects of PQQ supplementation on the growth performance or body composition of growing rats ( 18 , 19 ) .…”
Section: Discussionmentioning
confidence: 99%
“…The potential number of catalyst cycles is approximately 2000, and four catalytic cycles of ascorbic acid have been reported ( 5 ) . Due to its antioxidant properties ( 11 ) , PQQ further exerts a neuroprotective and peritoneal protective action against mammalian oxidative stress ( 12 ) .…”
mentioning
confidence: 99%
“…Lipid peroxidation not only damages DNA, protein, and membrane lipids but also decreases feed utilization and growth performance ( Liang et al., 2015 ). Broilers are easily exposed to cumulative oxidative by-products through oxidized oil intake, resulting in an imbalance of redox status especially in the liver, which is the target organ for detoxication ( Wang et al., 2016 ). Oxidized fish oil diet also caused microbial disorder and decreased the species richness and intestinal microbial diversity in fish ( Peng et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…The use of PQQ in nutrition is increasingly being discussed in the literature [13,21]. Zhang Unlike in humans, the weaning process for pigs involves an abrupt dietary shift from sow milk to a completely feed-based diet, which consequentially inhibits the intestinal architecture and function, resulting in gut associated disorders, such as in ammation and diarrhea [23].…”
Section: Discussionmentioning
confidence: 99%